'Tele-observation' (with mobile phone) of infants discussed in online infant observation seminars during the 'new normal' of the Covid-19 pandemic. Issue 1 (3rd May 2020) - Daghighi, Sudabeh; Amini, Mozhgan; Dodangeh, Niloufar; Hashemzadeh, Mona; Kiani Dehkordi, Mansoureh; Nekouei Shoja, Nasim
ABSTRACT: The paper is a reflection on the collective experience of a group of observers were observing infants in Tehran, during the 'lockdown' period because of the Covid-19 pandemic. All continued their observations using a video link, called 'tele-observation'. The observers were doing either their first or second year at infant observation in a course at Tehran University of Medical Sciences with babies from seven months to one and a half years old. The younger babies assisted their observers because they were not mobile, while some older ones were mobile, and some were walking; therefore, able to move out of range of the video link. The technology used was a simple cellphone camera using 'WhatsApp'. The writers discuss the interrelation of two different arenas, the arena of technology and the emotional arena of infant observation. Three significant areas are covered, the observer-mother relationship, the observer-infant relationship and the mother-infant relationship. The authors do not enter into the field of theory, because their aim is to focus on their raw experiences in using video-link instead of observations in person, because of the unprecedented challenges to face to face contact created by a world pandemic.